Development of a Digital-Based Village Library to Increase Community Literacy in Ngajaran Hamlet - Fitriah M. Suud; Isnanita Noviya Andriyani (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
The library is an indispensable tool to increase children's interest in reading. especially the village library is a facility that is needed by the community. But so far there are still many village libraries that are still constrained in their operations. This service aims to provide digital library management training and also to increase public interest in reading. The process of this service activity takes place in 3 stages. The first is the provision of library data input training. Previously, the servant handed over a laptop unit to the Matahati village library. This is because all library activities are carried out manually. So that the servant took the initiative to provide digital devices that could be used for library management needs as expected. Library management became more organized after the SLims (Senayan Library Management System) application was installed on the devices that have been submitted, which is an open source software used to manage libraries digitally. The second process in this service is to hold library management training. This training is considered very important for library managers and also other visitors. Cataloging and presentation of collections/shelving has become more organized and systematic. Apart from focusing on digital library management, this service also aims to increase children's interest in reading. Therefore, in addition to holding library management training events for administrators and the local community, the process of the three servants holding several competition activities for Sidomulyo village children which aims to increase their love for visiting the library and can increase their interest in reading.